2017
DOI: 10.1038/s41598-017-04897-x
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in BRCA2 and taxane resistance in prostate cancer

Abstract: Mutations in BRCA1 or BRCA2 define a subset of prostate cancer patients. Herein, we address the question whether BRCA1/2 mutations have a predictive impact on chemotherapy with docetaxel, a widely used drug in patients with metastatic castration resistant prostate cancer (mCRPC). Fifty-three men treated with docetaxel for mCRPC were tested for somatic BRCA1/2 mutations of the primary tumor. In a subgroup of patients, BRCA1/2 protein expression was tested as a potential surrogate marker for BRCA1/2 inactivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 41 publications
2
31
0
1
Order By: Relevance
“…A high pCR rate after neo-adjuvant anthracycline-taxane therapy was also demonstrated in BRCA1/2-mutated triple-negative breast cancer (n = 53) 240. Mutations in BRCA2 have a negative impact on the response rate to docetaxel in metastatic castration resistant prostate cancer (mCRPC) (n = 53) although no correlation was found between BRCA1/2 protein expression and response to treatment 241. Another large multi-institutional retrospective comparison of mCRPC patients (n = 390) with and without germline mutations in DNA repair genes (including BRCA2, ATM, CHEK2, BRCA1, PALB2, RAD51D and others) showed no difference between mutation carriers and non-carriers in their therapy response, progression-free survival after docetaxel or anti-androgen treatment and overall survival 242.…”
Section: Perspectives For the Treatment Of Patients With Brca Mutationsmentioning
confidence: 99%
“…A high pCR rate after neo-adjuvant anthracycline-taxane therapy was also demonstrated in BRCA1/2-mutated triple-negative breast cancer (n = 53) 240. Mutations in BRCA2 have a negative impact on the response rate to docetaxel in metastatic castration resistant prostate cancer (mCRPC) (n = 53) although no correlation was found between BRCA1/2 protein expression and response to treatment 241. Another large multi-institutional retrospective comparison of mCRPC patients (n = 390) with and without germline mutations in DNA repair genes (including BRCA2, ATM, CHEK2, BRCA1, PALB2, RAD51D and others) showed no difference between mutation carriers and non-carriers in their therapy response, progression-free survival after docetaxel or anti-androgen treatment and overall survival 242.…”
Section: Perspectives For the Treatment Of Patients With Brca Mutationsmentioning
confidence: 99%
“…Library preparation and semiconductor sequencing was performed as described earlier (17,18). In short, for both panels amplicon libraries were prepared using two primer pools with 5/10 ng of DNA and the Ion AmpliSeq Library Kit v2.0 (Thermo Fisher Scientific), respectively.…”
Section: Brca1 Brca2 As Well As Atm Atr Bard1 Brip1 Chek1 Chekmentioning
confidence: 99%
“…A cell-line study on BRCA2m and TP53 wt OC showed high sensitivity to taxanes and platinum agents [77] although the clinical relevance of these findings is unclear and with limited retrospective data available suggesting no difference in response according to BRCA1/2 status [97]. Retrospective studies do suggest lower response to taxanes in s BRCA2m prostate, and BRCA1m breast cancer patients [98,99]. The relationship between taxane sensitivity and BRCA m in OC requires further investigation.…”
Section: Treatment Of Ovarian Cancer and Implications Of Brca1/2 Statusmentioning
confidence: 99%